Calibration method to assess the accuracy of measurement devices using the theory of uncertainty. (2nd December 2014) - Vasilevskyi, O. M.
Abstract : The development of evaluation methods for precision measurement and inter-verification interval measurement for measurement devices based on the concept of the uncertainty of measurement is needed in order to establish the timing of the next scheduled or unscheduled verification of the correspondence of metrological characteristics to their standardised values. The definition of the timing (periodicity) of the metrological verification of measurement devices as used in business or health care, while monitoring environmental conditions and proving health and safety at work, is an urgent issue in scientific research, upon which depends the quality of goods and services. A method of evaluating the accuracy of measurements and the inter-verification interval for measurement devices is proposed, based on using international standards guidelines for quality measurement. The calibration method for evaluating the inter-verification interval of measurement devices was tested during the metrological certification of the measurement device for the moment of inertia of electric motors.